STRATEGIC CHANGES IN THE SOCIO-CULTURAL LEVEL. CONTEMPORARY SOCIETY, BETWEEN "UNITY IN DIVERSITY" AND DISSOLUTION IN DIVERSITY - Ramona-Gabriela EANA (Strategii Manageriale)
Change existed in various forms in all stages of development of human society, is that we were dealing with in all economic aspects, social, cultural or others, all of which have affected human existence. A complex phenomenon, which occurs in a longer or shorter period of time and which requires humans to be located in the center, through their own will, constituted into a veritable binder between cause and effect, old and new, nature and culture. Today the exchange of cultural information in the context of international system allows groups of people to interact generating complex changes, so it is essential to take into account processes that could limit diversity in evolution. As well as the cultural phenomenon develops by increasing its social size, density and diversity, society will always be interested in the way how every new element changes human individual universe.